2020
DOI: 10.1155/2020/7546954
|View full text |Cite
|
Sign up to set email alerts
|

Mother’s Knowledge on HIV, Syphilis, Rubella, and Associated Factors in Northern Tanzania: Implications for MTCT Elimination Strategies

Abstract: Background. Infections transmitted from mother to child (MTCT) during pregnancy, childbirth, and breastfeeding contribute significantly to the high infant and childhood morbidity and mortality in sub-Saharan African countries. The most significant and preventable of these include HIV, syphilis, and rubella. To achieve elimination, mothers need to be aware of and to understand effective preventive measures against these infections. Lack of comprehensive knowledge on transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
(104 reference statements)
0
1
0
1
Order By: Relevance
“…However, reports of heterosexual syphilis transmission have been increasing since 2014 (National Institute of Infectious Diseases (Japan) 2020 ); in parallel, the number of reported cases of congenital syphilis has shown an increasing trend (National Institute of Infectious Diseases (Japan) 2021 ). A previous study showed that 27.8% of mothers in Tanzania knew that syphilis can be transmitted to their children during pregnancy (Chotta et al, 2020 ). Another study in Bangladesh showed that 13% of women had knowledge about syphilis and there was association about awareness of syphilis with age, residential location, educational level, and socioeconomic status (Hossain et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, reports of heterosexual syphilis transmission have been increasing since 2014 (National Institute of Infectious Diseases (Japan) 2020 ); in parallel, the number of reported cases of congenital syphilis has shown an increasing trend (National Institute of Infectious Diseases (Japan) 2021 ). A previous study showed that 27.8% of mothers in Tanzania knew that syphilis can be transmitted to their children during pregnancy (Chotta et al, 2020 ). Another study in Bangladesh showed that 13% of women had knowledge about syphilis and there was association about awareness of syphilis with age, residential location, educational level, and socioeconomic status (Hossain et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…(G7) Diante das falas, as participantes demonstraram frágil conhecimento sobre a possibilidade de transmissão da sífilis para o seu filho. O mesmo foi observado em estudo, que evidenciou que gestantes, com Venereal Disease Research Laboratory (VDRL) positivo, não possuem conhecimento quanto à transmissão da doença aos filhos (18,19) .…”
Section: Orientações Sobre a Prevenção Da Sífilis Na Gestaçãounclassified